Mechanical performance of a particleboard based on natural hardener. Issue 2 (4th March 2023) - Ndiwe, Benoit; Konai, Noel; Pizzi, Antonio; Karga, Lionel; Kaoutoing, Maxime D.; Danwe, Raidandi
ABSTRACT: This work valorizes bio-hardeners from the Far North region of Cameroon, such as the exudates of Senegalia senegal, Vachellia seyal, Acacia siebteriana, and Vachellia nilotica . They were used to manufacture particleboard based on Maritime pine tannin resin, marketed to find a palliative solution to the environmental problems posed using synthetic hardeners such as paraformaldehyde. The rigidity values of the tannin resin vary from 4337 MPa at 154°C for the lowest to 5341 MPa for the highest at pH =  3.5. The behavior of the manufactured 13 mm thick particleboards of medium density was determined by calculating the variation of the bending strength (MOR), modulus of elasticity (MOE), and internal bond (IB) as a function of densities. The values of MOE vary between 1960.20 MPa and 3067.93 MPa and those of MOR between 13.17 MPa and 20.39 MPa. The maximum values of IB and Brinell hardness (HB) are 0.60 MPa and 3.78 daN/mm2 respectively. These physical and mechanical properties increased with increasing densities. The particleboards made with these bio-hardeners had better properties than those made with paraformaldehyde as hardener. The particleboard made with Vachellia nilotica exudate had the best physical and mechanical properties.